2015
DOI: 10.1093/ehjci/jev009
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial efficiency is an important determinant of functional improvement after aortic valve replacement in aortic valve stenosis patients: a combined PET and CMR study

Abstract: MEE is significantly reduced in patients with AVS-induced hypertrophy. Improved MEE is an important predictor of AVR-induced improvement of exercise capacity in AVS patients. Future investigation is needed to confirm our observations in a large prospective, multicenter clinical trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…These studies were also restricted by the absence of methods or by inaccurate methods to quantify stroke work, which evidently hampers any firm conclusion of how AS may affect myocardial efficiency. A more recent study found normal MVO 2 and reduced myocardial efficiency in 10 symptomatic AS patients with preserved LVEF compared with a younger control group (32% versus 49%) 28. Notably, myocardial efficiency for controls was substantially higher than that shown in previous reports (≈15–30%), and the reliability of this conclusion may be questioned 7…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…These studies were also restricted by the absence of methods or by inaccurate methods to quantify stroke work, which evidently hampers any firm conclusion of how AS may affect myocardial efficiency. A more recent study found normal MVO 2 and reduced myocardial efficiency in 10 symptomatic AS patients with preserved LVEF compared with a younger control group (32% versus 49%) 28. Notably, myocardial efficiency for controls was substantially higher than that shown in previous reports (≈15–30%), and the reliability of this conclusion may be questioned 7…”
Section: Discussionmentioning
confidence: 93%
“…The pathophysiology of myocardial hypertrophy and the progression to LV failure in AS patients is a matter of ongoing debate,26, 27 and impaired MVO 2 capacity, limited substrate accessibility, and energy transfer or utilization have been proposed as responsible adverse mechanisms 5, 9, 28. However, clinical studies on MVO 2 and MEE during the progression from compensated hypertrophy to heart failure are lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that LV unloading improves coupling between mitochondrial energy production and stroke work, a finding which is supported by increasing myocardial efficiency in patients with AS who undergo AVR. 36 However, despite this evident relationship between afterload and myocardial efficiency, there was no overall improvement in MEE for patients treated with metoprolol ( Figures 2F and 4F). This may be explained by the fact that we investigated patients with asymptomatic AS who in contrast to AS patients with heart failure may have a normal or near-normal MEE.…”
Section: Effects Of Metoprolol On Cardiac Energeticsmentioning
confidence: 93%
“…35 Similarly, the transition from compensated hypertrophy to failure in patients with AS is characterized by reduced myocardial efficiency caused by an increase in total MVO 2 (ie, MVO 2 ×LV mass) and an inability to maintain stroke work. 10,36 Thus, a combination of hemodynamic and metabolic overload contributes to the onset of heart failure in patients with AS.…”
Section: Effects Of Metoprolol On Cardiac Energeticsmentioning
confidence: 99%